2019
DOI: 10.4034/pboci.2019.191.90
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Caries and Periodontal Disease Among Indonesian Pregnant Women

Abstract: Objective: To determine the extent of bleeding on probing, probing pocket depth and the level of oral hygiene and caries prevalence among pregnant women. Material and Methods: Random samples of pregnant women attending eight public health centers were examined. Their periodontal and caries statuses were examined using the Community Periodontal Index, Simplified Oral Hygiene Index and DMF-T. The good criteria of OHI-S ranged from 0 to 1.2, the fair from 1.3 to 3.0 and the poor from 3.1 to 6.0. Descriptive stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
3
1
6
Order By: Relevance
“…In the current study, over half of the patients had also experienced dental caries during their pregnancy. This incidence is lower than a previous study conducted in Indonesia, where it was estimated that the incidence of dental caries in pregnant women was 84.7% 7 . A previous study by Azofeifa et al demonstrated that there was no significant difference in the incidence of dental between pregnant and non-pregnant women; however, the incidence of untreated dental caries is much higher in pregnant women 8 .…”
Section: Prevalence Of Dental Problems During Pregnancycontrasting
confidence: 63%
“…In the current study, over half of the patients had also experienced dental caries during their pregnancy. This incidence is lower than a previous study conducted in Indonesia, where it was estimated that the incidence of dental caries in pregnant women was 84.7% 7 . A previous study by Azofeifa et al demonstrated that there was no significant difference in the incidence of dental between pregnant and non-pregnant women; however, the incidence of untreated dental caries is much higher in pregnant women 8 .…”
Section: Prevalence Of Dental Problems During Pregnancycontrasting
confidence: 63%
“…During pregnancy, women experience several hormonal shifts. Previous evidence has shown that high estrogen and progesterone levels, associated with inadequate oral hygiene, can lead to PD [41]. Most pregnant women who enrolled in this study (78.57%) presented PD, and 50% had chronic periodontitis.…”
Section: Plos Onementioning
confidence: 71%
“…Hasil RISKESDAS tahun 2018 tersebut menunjukkan persentase kasus periodontitis di Indonesia sebesar 74,1% (Riset Kesehatan Dasar (RISKESDAS), 2019). Menurut penelitian Tedjosasongko (2019) yang melakukan survey prevalensi penyakit periodontal pada 98 wanita hamil di Indonesia, didapatkan sekitar 63% diantara responden mengidap penyakit periodontal (Tedjosasongko et al, 2019).…”
Section: Pendahuluanunclassified